2004
DOI: 10.1002/polb.20271
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of clay modifications and compatibilizers on the formation and physical properties of melt‐mixed polypropylene/clay nanocomposites

Abstract: The melt mixing technique was used to prepare various polypropylene (PP)‐based (nano)composites. Two commercial organoclays (denoted 20A and 30B) served as the fillers for the PP matrix, and two different maleated (so‐called) compatibilizers (denoted PP‐MA and SMA) were employed as the third component. The results from X‐ray diffraction (XRD) and transmission electron microscope (TEM) experiments revealed that 190 °C was an adequate temperature for preparing the nanocomposites. Nanocomposites were achieved onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 31 publications
3
63
0
2
Order By: Relevance
“…TGA curves do not show weight loss below 200 o C, as shown in the Figure 8, indicating that no water or residual solvent remained in the samples. Because of some organic molecules in interlayer spaces, clay began to lose weight at 230 o C and finally had 30.0 wt% losses at 600 o C at two different conditions, similar to the results reported by Chiu et al [12]. In air condition, no oxidation occurred for nanocomposites until 270 o C, TLCP and TC3 curves follow the same route but TC25 and TC50 followed another route.…”
Section: Thermal Stabilitysupporting
confidence: 79%
“…TGA curves do not show weight loss below 200 o C, as shown in the Figure 8, indicating that no water or residual solvent remained in the samples. Because of some organic molecules in interlayer spaces, clay began to lose weight at 230 o C and finally had 30.0 wt% losses at 600 o C at two different conditions, similar to the results reported by Chiu et al [12]. In air condition, no oxidation occurred for nanocomposites until 270 o C, TLCP and TC3 curves follow the same route but TC25 and TC50 followed another route.…”
Section: Thermal Stabilitysupporting
confidence: 79%
“…No weight loss occurred below 200 o C in any of the samples. Because of the presence of some organic molecules in interlayer spaces, the clay began to lose weight at 230 o C; at 600 o C, the clay weight loss was 30 %, similar to the result reported by Chiu et al [23] Comparing TLCP with TC3 white, the thermal stability of TC3 white increased. For example, for TLCP, the temperature at which the weight loss started was 335 o C whereas for TC3 white, it was 349 o C. For TLCP, the temperature at which the weight loss was halved was 530 o C and for the nanocomposite, it was 549 o C. TLCP used here was a semicrystalline nematic forming TLCP.…”
Section: Thermal Propertiessupporting
confidence: 78%
“…Shear processing with ultrasonication or conventional compounding equipment will decrease the nanocomposite formation time by disruption of primary particles and establishing composite uniformity [10]. Disappearance of peaks in clay PP composites sug- [41]. The same authors demonstrated exfoliation with poly(styreneco-maleic-anhydride) (PS-g-MA) oligomer as compatibilizer instead of PP-g-MA.…”
Section: Gas Tortuous Theorymentioning
confidence: 87%